High-Throughput Screening of a Functional Human CXCL12-CXCR4 Signaling Axis in a Genetically Modified S. cerevisiae: Discovery of a Novel Up-Regulator of CXCR4 Activity - Murphy, James W.; Rajasekaran, Deepa; Merkel, Janie; Skeens, Erin; Keeler, Camille; Hodsdon, Michael E.; Lisi, George P.; Lolis, Elias (Frontiers in Molecular Biosciences, 2020)
CXCL12 activates CXCR4 and is involved in embryogenesis, hematopoiesis, angiogenesis, and has pathological roles in HIV-1, WHIM disease, cancer, and autoimmune diseases. An antagonist, AMD3100, is used for release of CD34+ hematopoietic stem cells from the bone marrow for autologous transplantation for lymphoma or multiple myeloma patients. Adverse effects are tolerated due to its short-term treatment, but AMD3100 is cardiotoxic in clinical studies for HIV-1. In an effort to determine whether S. cerevisiae expressing a functional human CXCR4 could be used as a platform for identifying a ligand from a library of less ~1,000 compounds, a high-throughput screen was developed. We report that 2-carboxyphenyl phosphate (fosfosal) up-regulates CXCR4 activation only in the presence of CXCL12. This is the first identification of a compound that increases CXCR4 activity by any mechanism. We mapped the fosfosal binding site on CXCL12, describe its mechanism of action, and study its chemical components, salicylate and phosphate, to conclude they synergize to achieve the functional effect.